Forging a global environmental agreement through trade sanctions on free riders? - Thomas Eichner; Rüdiger Pethig (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper studies the formation of self-enforcing global environmental agreements in a world economy with international trade and two groups of countries that differ with respect to fuel demand and environmental damage. It investigates whether the signatories threat to embargo (potential) free riders secures all countries participation in the agreement. Resorting to numerical analysis, we find that an embargo may be unnecessary, ineffective or even counterproductive - depending on the degree of asymmetry and other parameters. On some subset of parameters, the embargo stabilizes the otherwise unstable global agreement, but the threat of embargo is not credible. However, in some of these cases credibility can be restored by suitable intra-coalition transfers.
Keywords: F18; Q37; Q58; 330